Identification of cultural acculturation in the documentary film “Jelajah Budaya Tionghoa Nusantara” by DAAI TV - Sutandi, Septerianie; Selvia, Selvia (Universitas Dian Nuswantoro, 2025)
Since 600 years ago, due to Indonesia’s very strategic position, Indonesia has become one of the centers of trade and cultural exchange in the Pacific Ocean. Because many traders from China landed in several areas in Indonesia, there were many phenomena of local cultural acculturation with Chinese culture. The acculturation process occurs because of social contact from one culture to another or the native culture with the culture of immigrants. This research is a qualitative descriptive research that analyzes the pattern of local cultural acculturation with Chinese culture in each episode of the documentary film